2009
DOI: 10.1111/j.1467-8535.2008.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐mediated discussion, self‐efficacy and gender

Abstract: In the context of hybrid instruction, this study was designed to explore whether gender has an influence on learners' preferences for synchronous or asynchronous modes of computer-mediated communication, and whether this decision impacts learners' self-efficacy (SE) towards knowledge acquisition. The participants were 180 teacher-education students (151 females and 29 males) enrolled in a hybrid (blend of traditional classroom instruction and online learning activities) foundations course at a United States re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Similarly, the participating adolescents reported watching television as a leisure activity, as is the case with most adolescents, regardless of cultural background (Lin & Overbaugh, 2009). Even so, while Australia recently introduced educational television programming directed at Indigenous children (Lonsdale, 2010) and Indigenous television dramas are increasingly available (Knox, 2012), as a new Indigenous media landscape continues to emerge (Rennie & Featherstone, 2008), current findings would suggest that television plays a relatively minor role in the lives of the participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the participating adolescents reported watching television as a leisure activity, as is the case with most adolescents, regardless of cultural background (Lin & Overbaugh, 2009). Even so, while Australia recently introduced educational television programming directed at Indigenous children (Lonsdale, 2010) and Indigenous television dramas are increasingly available (Knox, 2012), as a new Indigenous media landscape continues to emerge (Rennie & Featherstone, 2008), current findings would suggest that television plays a relatively minor role in the lives of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…DeBell and Chapman (2006) similarly point to positive outcomes for internet use, suggesting it promotes cognitive development, "specifically in the area of visual intelligence, where certain computer activities --particularly games --may enhance the ability to monitor several visual stimuli at once, to read diagrams, recognize icons, and visualize spatial relationships" (p. 3). Of particular relevance to the findings of the current study, Durkin, Conti-Ramsdent and Walker (2011) Although screen technology use can be associated with positive developmental and educational consequences, including the development of digital literacy, the outcomes appear to be mediated by a variety of individual characteristics (Homer, Hayward, Frye, & Plass, 2012;Johnson, 2011), life circumstances (Hilbert, 2011) and a number of other factors, including: age (Lee, Bartolic, & Vandewater, 2009;Roberts & Foehr, 2008;Rideout, 2011;Warburton & Highfield, 2012); gender (Lin & Overbaugh, 2009;Vekiri & Chronaki, 2008;Zhong, 2011); place of residence, especially urban versus rural locations (Velaga, Beecroft, Nelson, Corsar, & Edwards, 2012), ethnicity and social-economic background (Hargittai, 2008). For example, in one study reading skills were found to improve with internet use, but only for those youth who began with low level reading skills (Jackson, von Eye, Witt, Zhao & Fitzgerald, 2011).…”
mentioning
confidence: 99%
“…A Likert questionnaire to measure the six constructs (i.e., awareness knowledge, procedural knowledge, attitude, perceived usefulness, actual use and intention to use) was developed. The items were adapted from those previously used in Davis (1989), Chen et al (2008), Venkatesh (2000), Hu and Chau (2001), Lin and Overbaugh (2009), and Taylor and Todd (1995). The questionnaire in all contained 32 items measuring all the six constructs under study.…”
Section: Instrumentmentioning
confidence: 99%
“…The obtainability to choose communication modes seems to influence learners' self-efficacy (SE) which consequently affects learning motivation (Brophy, 2004;Zimmerman, 2000). Specifically, the delayed, asynchronous communication typically utilizes discussion board built upon course management systems, blogs or even Wikipedia-type communication tools, whereas synchronous discussions require instant messaging type of tools (Lin & Overbaugh, 2009). With aid of ICT to facilitate hybrid instruction or pure online learning, immediate communication and interaction indeed offers great flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…In light of time management, procrastination as in individual differences has been recognized as one of the most important in learning settings (Michinov, Brunot, Le Bohec, Juhel, & Delaval, in press). As for different communication venue, real-time synchronous communication takes greater Internet bandwidth than delayed, asynchronous communication (Lin & Overbaugh, 2009). The obtainability to choose communication modes seems to influence learners' self-efficacy (SE) which consequently affects learning motivation (Brophy, 2004;Zimmerman, 2000).…”
Section: Introductionmentioning
confidence: 99%